Body mass index and body size in early adulthood and risk of pancreatic cancer in a central European multicenter case-control study - Urayama, Kevin Y; Holcátová, Ivana; Janout, Vladimír; Foretová, Lenka; Fabiánová, Eleonóra; Adamčáková, Zora; Ryska, Miroslav; Martínek, Arnošt; Shonová, Olga; Brennan, Paul; Scélo, Ghislaine (International journal of cancer, 2011)
The relationship between two measures of excess body weight, body mass index (BMI) and body size score, and risk of pancreatic cancer was examined among 574 pancreatic cancer cases and 596 frequency-matched controls from the Czech Republic and Slovakia enrolled between 2004 and 2009. Analyses using multivariable logistic regression showed an increased risk of pancreatic cancer associated with elevated quartiles of BMI at ages 20 [fourth quartile: odds ratio (OR) = 1.79, 95% confidence interval (CI): 1.23, 2.61] and 40 (fourth quartile: OR = 1.57, 95% CI: 1.09, 2.27) compared to the lowest quartile. Consistent results were observed for body size score at ages 20 (high versus low: OR = 1.66, 95% CI: 1.08, 2.57) and 40 (medium versus low: OR = 1.36, 95% CI: 1.00, 1.86), but no association was found for BMI and body size score at 2 years before the interview. Stronger risk estimates for BMI were observed in males than females, particularly at age 20, but the analysis of body size yielded similar estimates by sex. When considering excess body weight at both ages 20 and 40 jointly, the highest risk estimates were observed among subjects with elevated levels at both time periods in the analysis of BMI (OR = 1.86, 95% CI: 1.32, 2.62) and body size (OR = 1.53, 95% CI: 1.09, 2.13). These findings, based on two different measures, provide strong support for an increased risk of pancreatic cancer associated with excess body weight, possibly strongest during early adulthood. Copyright 2011 UICC.
Keywords: dospělí; velikost těla; Female; Adult; ženské pohlaví; mladý dospělý; Pancreatic Neoplasms; Slovakia; lidé; Body Size; nádory slinivky břišní; studie případů a kontrol; Aged, 80 and over; Risk Factors; tělesná hmotnost; Male; Case-Control Studies; Aged; Czech Republic; Young Adult; index tělesné hmotnosti; rizikové faktory; Body Weight; Česká republika; lidé středního věku; senioři nad 80 let; Slovenská republika; senioři; mužské pohlaví; Body Mass Index; Middle Aged; Humans